Сhange in mentality towards disabled people in Сentral Asia - Xalikulova Xulkar Yuldashevna (Zien Journals, 2023)
In early societies, the disabled occupied the position of flawed, inferior, poor people: they were considered a burden, people unable to benefit. But before the Zorastrian religion, the idea of physical defects was understood as a punishment for sins or as a sign of possession by evil spirits. This attitude towards the disabled often led to the fact that they were shunned, feared and considered outcasts of society. The daily lifestyle of people with physical and mental disabilities in those days turned into restriction and isolation, their exclusion from normal life, labor relations, creative spheres. This article is about the tolerant attitude of people to the disabled. This is done in the Avestan meaning in relation to persons with disabilities. Since ancient times, people in the east have been treated with tolerance. The nature of the attitude towards disability and the life of each nation is based on the mentality and religious relations of this nation.In particular, in Central Asia in ancient times, human life was determined on the basis of religious beliefs. For example, there was a pre-Islamic religion Zorastrianism. It has the words "good thoughts, good words, good work." This is proof of a tolerant attitude towards disabled people. The Holy Book of Zoroastrianism in Avesto also calls for tolerance attitude.
Keywords: Avesto; vendidat; poor; blind